Netralisasi Perempuan Pekerja Seks Komersial (Studi Pada Tiga Perempuan Pekerja Seks Komersial di Kota Pekanbaru - Anggun Refliana; Rio Tutrianto (Sisi Lain Realita, 2023)
The phenomenon of commercial sex workers is an interesting thing tostudy, because this phenomenon continues from the past until now. Like the phenomenon of commercialsex workers in Pekanbaru City. Theproblem of commercial sex workers or prostitution has been around for along time, since there are many places of entertainment, be it cafes, dimly lit stalls, massage parlors and some are set up on the sides of roads or shops. Currently, more and more entertainment venues are located inevery corner of Pekanbaru City.Through a qualitative approach, byconducting interviews with severalselected sources, this researchexplains that. Using the theory ofneutralization techniques, it can be explained that a woman may choose to become a prostitute not only foreconomic or social reasons, but also because of their ability to neutralizefeelings of guilt and maintain apositive self-image. Neutralizationtechniques allow individuals to justify their actions in a way that makes them feel more comfortableand less guilty. By understandingthese techniques, it can be seen that a woman's decision to become a prostitute is often the result of a complex series of justifications that enable them to deal with the stigma and social pressures associated with the work. It also suggests that efforts to address the problem of commercial sex work need to consider not only economic and social factors but also the ways inwhich individuals psychologicallyneutralize their actions.